SINERGITAS PEMERINTAH DAERAH KABUPATEN KEPULAUAN MERANTI DALAM PENGELOLAAN SAMPAH TAHUN 2015 - Ria Riska Puspitasari; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine how the synergy District Government Kepulaun Meranti in waste management. This study uses qualitative research methods with descriptive research, which can be interpreted as a problem-solving process was investigated by describing the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories.Based on the results of this study concluded that synergy Kepulauan Meranti regency government in waste management in 2016 had not been effective. Waste management do Office Market, Hygiene and conducting collection and pengakutan rubbish you may have on household waste and rubbish commerce. While the Department of Public Works do the construction of roads and bridges to facilitate the flow of transport of transporting waste, construction of TPS made of concrete / cast to facilitate people throw garbage, construction of drainage as cleanup efforts drains so that the waste does not accumulate in trenches and facilitate attendant waste collector for membersihaknya, besides TPA to establish areas as intended. The Environment Agency only empower the community in waste management through education and training recycle waste, but these activities have not shown significant results in waste management in Kepulauan Meranti District. Obstacles in the waste management collide at the disposal site (TPA) which is narrow, while the new location is very remote and there is no access to the landfill. Infrastructure landfill (garbage cans) and freight transport was minimal. Human resources owned is still very limited does not correspond with the area. Management of waste management is still using the old pattern or the traditional ie the way in fuel. Not been determined by the regulatory / local regulations regarding waste management, so that the direction of waste management often choppy.Keywords: Synergy, Waste Management, Institutional